The Co-evolution of Honesty and Strategic Vigilance - Heintz, Christophe; Karabegovic, Mia; Molnar, Andras (Frontiers in Psychology, 2016)
We hypothesize that when honesty is not motivated by selfish goals, it reveals social preferences that have evolved for convincing strategically vigilant partners that one is a person worth cooperating with. In particular, we explain how the patterns of dishonest behavior observed in recent experiments can be motivated by preferences for social and self-esteem. These preferences have evolved because they are adaptive in an environment where it is advantageous to be selected as a partner by others and where these others are strategically vigilant: they efficiently evaluate the expected benefit of cooperating with specific partners and attend to their intentions. We specify the adaptive value of strategic vigilance and preferences for social and self esteem. We argue that evolved preferences for social and self-esteem are satisfied by applying mechanisms of strategic vigilance to one’s own behavior. We further argue that such cognitive processes obviate the need for the evolution of preferences for fairness and social norm compliance.